Metabolism, senescence, and natural products: new perspectives on wound healing in diabetes - Wu, Jingping; Yang, Qifeng; Cheng, Hongbin; Zheng, Huilan; Chen, Mingling (Frontiers in Nutrition, 2026)
Chronic diabetic wounds have become a major clinical challenge because of their difficulty in healing and high recurrence rate. This review proposes for the first time the theoretical framework of the “metabolism–senescence axis,” systematically elucidating the central role of cellular senescence in the mechanisms underlying the impaired healing of diabetic wounds. Research has indicated that systemic and local metabolic disorders caused by hyperglycemia and insulin resistance directly drive the senescence process of local wound cells through multiple mechanisms, including mitochondrial dysfunction, oxidative stress, and the accumulation of advanced glycation end products. The accumulated senescent cells further exacerbate inflammation, inhibit repair cell function, and disrupt angiogenesis through the secretion of the senescence-associated secretory phenotype (SASP), thereby forming a vicious cycle. In terms of therapeutic strategies, various interventions have been developed, such as the selective clearance of senescent cells, SASP functional regulation, and metabolic reprogramming of senescent cells. Among these, natural products exhibit unique and irreplaceable advantages because of their multicomponent and multitarget characteristics: they can directly affect senescent cells and the SASP, synergistically regulate core signaling pathways, and reprogram metabolism while modulating the local microenvironment. The systematic integration of traditional compound therapies provides a rich arsenal for targeting senescence in diabetic wound treatment. Concurrently, the application of innovative delivery systems, such as smart-responsive hydrogels and microneedles, has effectively overcome the clinical translation bottlenecks posed by the inherent physicochemical properties of natural products. With the deepening integration of multidisciplinary approaches, the therapeutic paradigm for diabetic wounds is shifting from traditional empirical models to precision medicine, opening new avenues to overcome the therapeutic impasse of diabetic chronic wounds and achieve functional tissue repair.